The scramble for Africa - Pakenham, Thomas (New York Random House, 1991)
In 1880 the continent of Africa was largely unexplored by Europeans. Less than thirty years later, only Liberia and Ethiopia remained unconquered by them. The rest-10 million square miles with 110 million bewildered new subjects-had been carved up by five European powers (and one extraordinary individual) in the names of Commerce, Christianity, 'Civillization and Conquest.
Includes bibliographical references (p. 697-703) and index.
Keywords: Africa-History-To 1884.